De novo truncating variants of TRIM8 and atypical neuro-renal syndrome: a case report and literature review - Wei Li; Hui Guo (BMC, 2023)
Abstract Background The TRIM8 gene encodes a protein that participates in various biological processes. TRIM8 variants can lead to early termination of protein translation, which can cause a rare disease called neuro-renal syndrome. This syndrome is characterized by epilepsy, psychomotor retardation, and focal segmental glomerulosclerosis. However, we found that some patients may not present the above typical triad, and the reason may be related to their variant sites. Case presentation We report a case of a 6-year-old boy with nephrotic-range proteinuria as the first prominent manifestation of TRIM8 variant. He had stage 3 chronic kidney disease at the time of presentation, specific facial features, and a neurogenic bladder. He had not experienced seizures previously. There were no apparent abnormalities in his growth, intelligence, or motor development. The results of whole exome sequencing showed a TRIM8 variant. Renal biopsy revealed focal segmental glomerulosclerosis and renal tubular cystic dilatation. He did not respond to hormone and angiotensin-converting enzyme inhibitor treatment; however, the symptoms of neurogenic bladder were relieved after treatment with Solifenacin. Conclusion In this case, renal disease was the prominent manifestation; the patient had no other obvious neurological symptoms except a neurogenic bladder. Notably, the variant site is the closest to the C-terminal to date. Based on the analysis of previously reported cases, we found that as the TRIM8 variant became closer to the C-terminal, the renal lesions became more prominent, and there were fewer neurologic lesions. Our findings provide a new understanding of neuro-renal syndrome caused by TRIM8 variant. Patients may only have kidney disease as a prominent manifestation. At the same time, we found that we should also pay attention to the eye lesions of these patients. Therefore, gene analysis is helpful in identifying the etiology and guiding the prognosis of patients with hormone-resistant proteinuria. We suggest that TRIM8 should be included in gene panels designed for the genetic evaluation of hormone-resistant proteinuria.